2006
DOI: 10.1007/s10545-006-0332-x
|View full text |Cite
|
Sign up to set email alerts
|

Breast feeding in IMD

Abstract: Breast feeding has proven benefits for many infants with inherited metabolic disorders (IMDs) but, with the exception of phenylketonuria, there are few reports in other conditions. A questionnaire, completed by dietitians and clinicians from 27 IMD centres from 15 countries (caring for a total of over 8000 patients with IMDs on diet) identified breast feeding experience in IMD. Successful, demand breast feeding (in combination with an infant amino acid formula free of precursor amino acids) was reported in 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
15

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 7 publications
(2 reference statements)
0
24
0
15
Order By: Relevance
“…[6][7][8][9][13][14][15] Even in the presence of certain risk factors for definitive weaning, which are inevitable in this situation, we consider that the breastfeeding duration of the children with PKU was very good and that it was comparable to the mean durations described in the literature, both for children with PKU and for Brazilian children without PKU. 13,16,17 Demirkol et al, 13 McCabe et al 10 and Motzfeldt et al 6 found mean breastfeeding duration in phenylketonuric patients of 6.1, 8.9 and 7.0 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][13][14][15] Even in the presence of certain risk factors for definitive weaning, which are inevitable in this situation, we consider that the breastfeeding duration of the children with PKU was very good and that it was comparable to the mean durations described in the literature, both for children with PKU and for Brazilian children without PKU. 13,16,17 Demirkol et al, 13 McCabe et al 10 and Motzfeldt et al 6 found mean breastfeeding duration in phenylketonuric patients of 6.1, 8.9 and 7.0 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…An international survey reported five infants with CBS deficiency who had received breast-feeds in combination with a Met-free AA infant formula (MacDonald et al 2006a, b). The principles are the same as for breast-feeding in PKU (Francis and Smith 1981).…”
Section: Recommendationsmentioning
confidence: 99%
“…The WHO/FAO/UNU (2007) recommendations can be used to guide the total protein requirements (WHO et al 2007) but PKU research suggests that higher protein intakes than the WHO recommendations are required to compensate for the sub-optimal bio-availability of L-AAs in current preparations (MacDonald et al 2006a, b). It is recommended that the L-AA supplement is split into three to four doses throughout the day to maximise nitrogen retention and achieve appropriate growth (Acosta 2010).…”
Section: Recommendationsmentioning
confidence: 99%
“…. Entretanto, para que a utilização do LM tenha êxito no tratamento da PKU, é necessário que os pacientes tenham consultas freqüentes no serviço de referência, possibilitando ajustes dietéticos constantes e controle metabólico adequado, evitando níveis indesejáveis de phe no sangue [6][7][8][9][13][14][15] . Mesmo na presença de alguns fatores de risco, inevitá-veis nesta situação, para o desmame definitivo, consideramos que a duração da amamentação das crianças com PKU foi muito boa e semelhante aos tempos médios descritos na literatura, tanto para crianças com PKU quanto para crianças brasileiras sem PKU 13,16,17 .…”
Section: Métodosunclassified